THE PROCESS OF GRADUAL DIVERSIFICATION IN REGIONAL AGRICULTURAL SYSTEMS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the issues of supplying the domestic market of Uzbekistan with high-quality food products by increasing production volumes, as well as strengthening the country’s export potential. In addition, special attention is paid to the specialization of regions in fruit and vegetable production and to the integration of producers into fruit and vegetable clusters and cooperatives.
Keywords: Food industry, agriculture, diversification, clustering, modernization